(untitled) (Applied Biological Research, 2016)
An in vitro experiment was conducted with two tomato (Solanum lycopersicum) genotypes (PKM 1 and TNAU THCO 3) to assess alleviation of salinity stress by seed treatment using plant growth regulators and nutrients under laboratory conditions. Salt stress was imposed at 60 mM concentration by using NaCl. Plant growth regulators like indole acetic acid (100 ppm), gibberellic acid (1 mM), benzyl aminopurine (50 ppm), salicylic acid (2 mM), ascorbic acid (100 ppm) and salts potassium chloride (1%) and calcium chloride (0.5%) were used to alleviate salinity effects. The study revealed that among ameliorants used, gibberellic acid showed significantly premier observations like highest germination percentage (76.7 and 86.7%), tolerance index (62 and 68.2%) and alpha amylase activity (11.02 and 11.55 μg maltose g-1 sample) in PKM 1 and TNAU THCO 3, respectively. Catalase activity was high (32.65 and 36.25 μg H2O2 g-1 min-1) in salicylic acid treatment. Hybrid tomato TNAU THCO 3 responded well to PGRs and nutrients than variety PKM 1.